Effects of mirror therapy combined with motor tasks on upper extremity function and activities daily living of stroke patients - Kim, Kyunghoon (J Phys Ther Sci, 2016)
[Purpose] The objective of this study was to investigate the effects of mirror therapy combined with exercise tasks on the function of the upper limbs and activities of daily living. [Subjects and Methods] Twenty-five stroke patients who were receiving physical therapy at K Hospital in Gyeonggi-do, South Korea, were classified into a mirror therapy group (n=12) and a conventional therapy group (n=13). The therapies were applied for 30 minutes per day, five times per week, for a total of four weeks. Upper limb function was measured with the Action Research Arm test, the Fugl-Meyer Assessment, and the Box and Block test, and activities of daily living were measured with the Functional Independence Measure. A paired test was performed to compare the intragroup differences between before training and after four weeks of therapy, and an independent t-test was performed to compare the differences between the two groups before and after four weeks of therapy. [Results] In the intragroup comparison, both groups showed significant differences between measurements taken before and after four weeks of therapy. In the intergroup comparison, the mirror therapy group showed significant improvements compared with the conventional therapy group, both in upper limb function and activities of daily living. [Conclusion] The findings of this study demonstrated that mirror therapy is more effective than conventional therapy for the training of stroke patients to improve their upper limb function and activities of daily living.